GranDIHC-BR 2025-2035 - GC2: Ethics and Responsibility: Principles, Regulations, and Societal Implications of Human Participation in HCI Research - Rodrigues, Kamila Rios da Hora; Carvalho, Luiz Paulo; Freire, Andre Pimenta; Pimentel, Maria da Graça Campos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
This Grand Challenge highlights the importance of Ethics in HCI and Computing, covering its concepts, theories, methods, and applications, as well as its relevance in research, teaching, and practice, considering the basic elements of Ethical consideration such as freedom, conscience, rationality, and accountability. The challenge includes but is not limited to, legal and practical issues of human involvement in HCI research. This Grand Challenge demands studies and advances with implications for HCI in the normative, applied and meta-scientific fields of Computer Ethics. The role of HCI is to promote debate and transform Computing, as a science and application, and to inform society on issues involving computational technologies, their consequences for human beings and other forms of life. This Grand Challenge points out that the HCI area must inform society and transfer the results of research, as one of the fundamental ethical aspects of the beneficence of participants. In this way, ethical and responsible research in HCI must reverberate in actions that direct scientific and technological development, the definition of public and regulatory policies, and their alignment with universal human rights and the constitution of more just and democratic societies. This paper is presented bilingually in English and Portuguese as a testament to its situated and universal implications.